An Institutional Based Cross Sectional Analytical Study on Nutritional Determinants of Low Birth Weight - Patel, Harsh; Mehta, Jitesh; Patel, Bela; Ram, Rohitkumar; Rathod, Mittal (International Journal of Innovative Research in Medical Science, 2023)
Background: Maternal nutrition during pregnancy is a key factor influencing birth outcomes. Pregnant women are at increased risk of various nutritional deficiencies, particularly in developing countries. Besides, most LBW infants in these countries are full-term newborns with intrauterine growth restriction due to maternal malnutrition and poor gestational weight gain. Objective: To study distribution of new-borns’ according to nutritional determinants of mothers’ and its association with low birth weight. Methods: An institutional based cross-sectional analytical study. New-borns delivered at study institute were considered as study participants. Estimated final sample size was 500. Sampling was done by Systemic random sampling method. Guardians (mothers) were face-to-face interviewed and also recorded data were collected from the case file and Mother and Child Protection (MCP) Card. Results: Majority newborns belonged to lower middle 194 (38.8%) and middle class164 (32.8%), More than two third (68.2%) newborns belonged to mothers who had pre pregnancy weight ≥45 kg, 86.4% from mothers whose height were ≥145 cm, 84.2% from mothers whose BMI ≥18.5 kg/m2, 65.6% newborns belonged to mothers whose weight gain were ≥ 9 kg, 18.2% from mothers who consume meals <3 times in a day, 82.8% from mothers who were anaemic, 85.2% and 79.4% taken regular IFA and calcium tablets respectively. Newborns belonged to mothers who were provided health education, supplementary nutrition, maternity benefits were 89%, 32%, 36.4% respectively. The odds of having LBW was significantly higher in lower and middle socioeconomic class, mothers with height <145 cm, BMI less than 18.5 kg/m2, weight gain less than 9 kg, consume <3 meals in a day and not received supplementary nutrition at anganvadi. Conclusion: The present study revealed that lower and middle socio-economic class, mothers with height <145 cm, BMI <18.5 kg/m2, <9 kg weight gain, consume <3 meals in a day and not received supplementary nutrition at anganvadi were statistically significant risk factors that associated for delivering LBW newborns.